(untitled) (AYUSHDHARA, 2025)
Chronic smoking remains a major public health challenge, often leading to irreversible morbidity despite cessation efforts. Conventional de-addiction treatment frequently fall short in addressing both the physiological dependence and the behavioral rituals associated with smoking. This case study presents the use of specially formulated Ayurvedic Medicated Dhoomvarti (herbal smoking cigarette) in a bit altered form as a Nicotine-free alternative for cigarette smokers aiming to quit, based on the classical Ayurvedic principle of Dhoompana, this altered medicated cigarette (Dhoomvarti) offers both behavioural and therapeutic support in managing nicotine dependence. In addition, the patient received oral administration of Vachadi Ghrita, a classical formulation with Medhya (cognitive-enhancing) and neuromodulatory properties, to support withdrawal management and mental clarity. The Intervention demonstrated progressive reduction in cigarette use, improved respiratory parameters, and resolution of withdrawal symptoms, suggesting that the use of this medicated cigarette may offer an effective complementary pathway in smoking de-addiction.